LOCAL RESOURCE-BASED POTENCIES IN PAMEKASAN REGENCY WITH ONE VILLAGE ONE PRODUCT APPROACH - Farahdilla Kutsiyah; Moh. Zali; Ummu Kulsum (Riset Ekonomi Pembangunan, 2021)
This article describes the potential of the Pamekasan Regency area by promoting local-based resources (endogenous development). The method applied: literature search, calculation of Location Quotient, observation and Focus group discussion. The results showed, the potential of the northern region: cattle, shallots, fish processing, tobacco, sonok beef cultural tourism destinations, biopharmaca, cayenne pepper, vegetables, coconut, furniture, bamboo, siwalan, buju’ bersila bersiti  tourism, catfish, tembang fish, shrimp paste. Southern region: salt, batik, tobacco, rice, anchovy, vanname shrimp, laying hens, processed fish (anchovies, selar) cattle fattening, tourism (jumiang beach, talang siring, fire never goes out), red chilies, krepek tette, marine tourism, oysters, mangrove, crab, small crab, seaweed, lorjuk, banana, rengginang, earthenware, sate lala ', krupuk (tack, fish, pulley), handicraft (bamboo, bag, skin), ampar stone religious tourism, broilers, tofu factories, peanuts, domestic chicken, herbal chilies, oranges, fresh fish restaurants, corn, shrimp, mackerel, herbal medicine, ball stadium, processed corn, green beans, drinks, vegetables, potoh, water tourism. Central region: agro-tourism (durian fruit, avocado klengkeng, mango, biopharmaca, Puncak Ratu Tour, Bukit Brukoh), batik, pebbles, cigarettes, pesantren-based economy, peanuts, crackers, plait, long beans, genting, bentoel, pepper, cayenne pepper, leeks, chips (cassava, taro, tette), beef, watermelon, cassava, coconut, banana, corn, brown sugar, chicken (laying eggs, domestic), siwalan, tape, rice, catfish.